Prevalence of Dentine Hypersensitivity in Vital Abutment Teeth being prepared for Fixed Partial Dentures or Crowns - Maria Komil Ghuuman; Miral Shad; Ammara Sharafat; Maira Afzal; Rida Anjum; Saira Ibrahim (Journal of Bahria University Medical and Dental College)
Objective: To determine the prevalence of dentine hypersensitivity during the preparation of vital abutment teeth for Fixed Partial Dentures or Crowns and its association with patient’s gender, age, and location of tooth.